Forum de Belem "Desafios Para a Pesquisa Florestal na Amazonia", Belem, 14 a 15 de Junho de 1999: palestras e resumos (Empresa Brasileira de Pesquisa Agropecuária, 2001)
This document is a compilation of abstracts and summaries from the forum on Chalenges for the Forestry Research in Amazonia, organized by Embrapa and CIFOR in June 1999 in Belem, Brazil. The main topic is sustainable management of the Amazonian forests. The discussions was divided into three sessions: 1. the first session is focused on big scale aspects of forest management such as forest policy, commercial exploitation of forests, industrial plantations. 2. the second session is more focused on local forest community level such as cooperative forest management, community forest management. 3. the third session debate was on global dimension and concern on Amazonian forest management such as globalization and the Brazilian Amazon, Amazonia and its role on the regional and global climate.